Knowledge and Utilization of Market-Oriented Agricultural Extension Service Among Farmers in Oyo State, Nigeria - Luqman, Akinbile; Salaudeen, Abdulrahman (Jurnal AGRISEP, 2024)
Market-oriented agricultural extension services (MOAES) are pivotal in transforming subsistence farming into a profitable and sustainable venture, thereby reducing rural poverty. This study investigates the knowledge and utilization of market-oriented agricultural extension services among farmers in Oyo State, Nigeria. The study employs a two-stage cluster sampling technique to select 106 farmers from four agricultural zones in Oyo State. Data was collected through structured questionnaires and interview schedules on knowledge, accessibility, utilization, and satisfaction with MOAES provided. The public extension (61.6%) was the primary provider of market-oriented agricultural extension services, with low knowledge and satisfaction. Utilization of the services on types of crops to grow, food safety standards, and sourcing of farm inputs were moderate. Overall utilization of MOAES by 55.7% of the farmers was low. Constraints were poor linkage (x̅=1.90), limited access to credit for input purchases (x̅=1.84), and inadequate price information for various inputs (x̅=1.68). Significant relationships existed between farmers sex (X2=3.259), marital status (X2=0.186), educational level of MOAES (X2=8.055). Strengthening the capacity of extension agents and focusing on value addition are recommended.